The effect of plantlet types and planting media on the growth of chrysanthemum (Chrysanthemum morifolium L.) plant seeds acclimatized in the lowlands ​ - Prayitno, Nova Putri Anggilia; Sukendah, Sukendah; Sulistyono, Agus (AGRICOLA, 2024)
The in vitro culture method can be used as a means of obtaining superior chrysanthemum seedlings. The aim of this research is to determine the best types of plantlets and types of planting media for the growth of chrysanthemum seedlings that are acclimatized in the lowlands. This research was in July-November 2022 at the Screenhouse located at Simowau Indah, Taman District, Sidoarjo Regency, East Java. This study employed a two-factor Completely Randomized Design (CRD), involving the type of plantlets and planting medium, with 12 treatment combinations repeated 3 times. The initial factor considered was the type of plantlet, featuring 3 treatments; whole plantlet, in vitro shoot plantlet and root plantlet. The second factor involved the type of planting medium with 4 treatments; husk charcoal (control), husk charcoal + soil (2:1), cocopeat + soil (2:1), and husk charcoal + cocopeat + soil (1:1:1). The results indicated that there was no interaction between planlet type and planting media across all observed parameters. Notably, the plantlet type treatment demonstrated the highest yield, particularly in terms of the percentage of survival and seedling height.